Answer:
Explanation:
x-intercepts are SOLUTIONS to a quadratic whereas when you put those solutions into factor form (in a set of parenthesis), you have the FACTORS of the quadratic. They are the same thing generally, they are just written in different forms. For example, if a solution to a quadratic is x = 3, it has been understood that x = 3 when y = 0. Therefore, if x - 3 = y and y = 0, then x - 3 = 0. Solving that for x, you get x = 3. That factor of x = 3 is (x - 3).
Following that logic, for a:
If the x intercepts are x = 0 and x = 3, it is understood that x + 0 = 0 so x = 0 and the factor is (x + 0) (it could also be x - 0 since adding 0 is the same as subtracting 0); if x = 3 it is understood that x - 3 = 0 and the factor is (x - 3).
For b:
If the x-intercepts are x = -1 and x = 1, then originally the factors were (x + 1) and (x - 1). Again, set each of those equal to 0 and solve for x (THE X-INTERCEPT EXISTS WHERE Y = 0!)
For c:
If the x-intercepts are x = -5 and x = 10, then originally the factors were (x + 5) and (x - 10).
For d:
If the x-intercept is a fraction, do the same thing:
x = 1/2 so
x - 1/2 = 0 Now multiply both the x and the 1/2 by a 2 to get the factor (2x - 1) and the other factor from x = 4 is (x - 4)